2003
DOI: 10.1046/j.0017-4815.2003.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐commerce, Transportation, and Economic Geography

Abstract: This paper explores possible ways in which growth in Internet retailing (e-retailing) may affect the spatial distribution of economic activities. After a brief overview of e-retailing, a categorization of possible spatial impacts is introduced. These include impacts on the retail industry, such as substitution of e-retail for brick-and-mortar retail, impacts on transportation, such as substitution of freight transportation for personal transportation in goods delivery, and pervasive impacts that affect the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 17 publications
3
60
0
6
Order By: Relevance
“…For freight transport it has been widely suggested that e-shopping will lead to more freight trips and more freight transport kilometres (e.g., Cohen, 2000;Dodgson et al, 2000;Golob and Regan, 2001;Nemoto et al, 2001;Anderson et al, 2003;Mokhtarian, 2004;Rotem-Mindali and Salomon, 2007). More freight transport kilometres are assumed because the Internet provides consumers with the opportunity to contact and purchase from distant retailers and manufacturers (Nemoto et al, 2001;Hesse, 2002;OECD, 2003;Mokhtarian, 2004;Visser and Lanzendorf, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…For freight transport it has been widely suggested that e-shopping will lead to more freight trips and more freight transport kilometres (e.g., Cohen, 2000;Dodgson et al, 2000;Golob and Regan, 2001;Nemoto et al, 2001;Anderson et al, 2003;Mokhtarian, 2004;Rotem-Mindali and Salomon, 2007). More freight transport kilometres are assumed because the Internet provides consumers with the opportunity to contact and purchase from distant retailers and manufacturers (Nemoto et al, 2001;Hesse, 2002;OECD, 2003;Mokhtarian, 2004;Visser and Lanzendorf, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Many studies in the above types of literature are conceptual contributions or literature reviews (see e.g. Guy, 1985;Salomon, 1985Salomon, , 1986Salomon and Koppelman, 1988;Mokhtarian, 1990Mokhtarian, , 2002Mokhtarian, , 2004Westlake, 1990;Rowley, 1996;Alba et al, 1997;Dholakia et al, 2000;Reynolds, 2000a, b;Gillespie et al, 2001;Golob and Regan, 2001;Lyons, 2002;Wrigley et al, 2002;Anderson et al, 2003;Burt and Sparks, 2003;Couclelis, 2004;Daduna and Lenz, 2004;Dholakia, 2004;Visser and Lanzendorf, 2004;Boschma and Weltevreden, 2005;Dixon et al, 2005). This paper draws on the work of Mokhtarian, which clearly delineates the concepts of substitution, complementarity, and other likely impacts of e-shopping.…”
Section: Introductionmentioning
confidence: 97%
“…This could be a problem because the choices for each channel could be influenced by different factors. Furthermore, differences exist with respect to the means of conveying information and maintaining customer relationships (for example, personalised product offerings) between the two channels (Anderson et al, 2003). Therefore, it is important to distinguish between the shopping modes.…”
Section: Literature Reviewmentioning
confidence: 99%